INTERNALISASI GURU DALAM MENANAMKAN NILAI KEDISIPLINAN MELALUI METODE KEPEMIMPINAN DI PAUD - Salsabila Arkana Kusumasanti (JIP: Jurnal Ilmu Pendidikan, 2026)
Early Childhood Education (PAUD) is a form of education that emphasizes the formation of a child's personality from an early age. The early childhood period, particularly between 0 and 6 years, is often known as the "Golden Age." At this age, children begin to develop cognitive, social, and emotional abilities that will influence their future lives. This level focuses not only on cognitive or academic aspects, but also emphasizes the formation of character and basic moral values ​​that will become provisions for the child's future. One aspect of character that is the main foundation and needs to be instilled from an early age is the value of discipline. This study uses a qualitative approach to understand in-depth the internalization of teachers in instilling the value of discipline through leadership methods in PAUD. The results of the study in PAUD show that each child is entrusted in turn as a daily leader (leading the line, prayer, ice breaking, Pancasila, cleanliness, and going home) and Monday ceremony officer (priority class B as a role model for class A). Teachers act as companions and supervisors on standby. Teachers use positive reinforcement (awarding stars/appreciation), direct feedback, and collaboration. These approaches can lead to overall improvements in discipline, including time management, behavior, learning, and social skills.